Cortical microstructural change linked to clinical recovery in subacute delayed encephalopathy after acute carbon monoxide poisoning: a longitudinal case report - Tamura, Takehiro; Fujimoto, Yuka; Nakamura, Hironobu; Takahashi, Yuki; Fujino, Junya; Takagi, Shunsuke; Takahashi, Hidehiko; Sugihara, Genichi (Frontiers in Toxicology, 2025)
Delayed encephalopathy after acute carbon monoxide poisoning (DEACMP) causes disabling cognitive–behavioral symptoms. While cortical atrophy is recognized as a correlate of long-term outcome, links between intracortical microstructural dynamics and clinical presentation remain largely unexplored. We followed a 51-year-old man with new-onset DEACMP for 5 months, using serial MRI combining cortical thickness with T1-weighted/T2-weighted (T1w/T2w) mapping as a proxy for intracortical microstructure. Despite progressive cortical thinning, T1w/T2w signals showed heterogeneous, region-specific trajectories. In the frontal networks, increases within premotor and dorsolateral prefrontal cortices aligned with improvements in executive function, whereas limited change in orbitofrontal/ventrolateral cortices was consistent with behavioral disinhibition. Overall, the clinical picture tracked more closely with intracortical signals than with morphometric atrophy. By combining T1w/T2w mapping with morphometry, this case provides the first longitudinal evidence of divergent cortical trajectories in subacute DEACMP—progressive thinning versus early intracortical improvement; confirmation in larger cohorts is warranted.